Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3923/jfas.2016.77.84
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Nickel and Mercury on Fatty Acid Composition in the Muscle of Fish Lates calcarifer

Abstract: In this study, the effect of nickel (Ni), mercury (Hg) and nickel plus mercury (Ni+ Hg) on fatty acid composition in the muscle tissues of fish Lates calcarifer has been investigated. It was determined from the results of 96 h metal exposure period of fish, depending on Ni, Hg and Ni plus Hg concentration, the amount of saturated fatty, mono unsaturated fatty acid and poly unsaturated fatty acids in fish were decreased when compared with control group (p<0.05). It was also found that Ni, Hg and Ni plus Hg had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The presence of chemical contaminants in the environment and feed in aquaculture areas may cause significant metal accumulation in aquaculture food products ( Tahity et al, 2022 ). Heavy metals are considered to be the most severe source of pollution in the aquatic environment due to their toxicity and absorption ( Senthamils et al, 2015 ). Heavy metal toxicity is determined by a number of parameters, including the dose, route of exposure, as well as age, gender, genetics, and nutritional state of those who have been exposed.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of chemical contaminants in the environment and feed in aquaculture areas may cause significant metal accumulation in aquaculture food products ( Tahity et al, 2022 ). Heavy metals are considered to be the most severe source of pollution in the aquatic environment due to their toxicity and absorption ( Senthamils et al, 2015 ). Heavy metal toxicity is determined by a number of parameters, including the dose, route of exposure, as well as age, gender, genetics, and nutritional state of those who have been exposed.…”
Section: Introductionmentioning
confidence: 99%
“…At 10,000× the WHO safety limit, the combination of the two metals resulted in haemolysis and caused a synergistic effect. A study on the synergistic effect of Ni and Hg on fatty acid composition in the muscle of fish conducted by Senthamilselvan et al (2016) found that at high concentrations of 0.8, 2.0 and 4.0 mg/L of Hg alone, Ni alone and Hg + Ni combination caused a decrease in fatty acid composition. Hg is a toxic and inhibitory metal in nature whilst Mn is an enhancer of growth at recommended WHO safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…Other metals/metalloids shown to have synergistic and/or antagonistic relationship with Hg include -Cr: e.g., synergistic action with Hg on fish (See: Selvan et al, 2012;Dwivedi et al, 2012); As: e.g., synergistic action in attenuating canonical and noncanonical NLRP3 inflammasome activation (See: Ahn et al, 2018); Pb: combined exposure (synergism) to Pb, inorganic Hg and MeHg showing deviation from additivity for cardiovascular toxicity in rats (See: Dwivedi et al, 2012) and Ni: synergistic effect of Ni and Hg on fatty acid composition in the muscle of fish Lates calcarifer (See: Senthamilselvan et al, 2016).…”
Section: Associations (Synergism/antagonism)mentioning
confidence: 99%